Evaluation of Hydraulic Jet Pump Application in Sembakung Field - Kunto Wibisono; Ratnayu Sitaresmi (Journal of Earth Energy Science, Engineering, and Technology, 2020)
Sembakung Field is an "brown" remote oil and gas field located in North Kalimantan with very limited road infrastructure to and within the location. The purpose of this study is to evaluate the performance of Hydraulic Jet Pump for field development as well as to assess the opportunities for incresing oil production by applying the Hydraulic Jet Pump in the fields. Quantitative data are used and evaluated to investigate the pump design and actual pump performance by considering transient and steady state conditions. The research is performed for three wells. There was significant difference between design and actual flowrate due to the transient and steady state conditions. Steady state condition was achieved within four to seven months in this field. Based on the evaluation results it can be concluded that the application of hydraulic jet pump is proper for Sembakung Field and there is opportunitiy to increase oil production rate by applying the pump type in the field. The application of the hydraulic jet pump during the period can produce 78 bpd to 112 bpd of oil with liquid production rates ranging from 130 bpd to 980 bpd.